PENGARUH KUALITAS LAYANAN, NILAI PELANGGAN, CUSTOMER RELATIONSHIP MANAGEMENT (CRM) TERHADAP KEPUASAN PELANGGAN DAN LOYALITAS PELANGGAN (STUDI PADA PT. BPR PRIMA MULTI MAKMUR) - Mochammad Faisal Fadli; Jonathan Giovanni (STIE 'INDONESIA' Pontianak, 2021)
This study aims to determine the effect of Service Quality, Customer Value, Customer Relationship Management (CRM) on Customer Satisfaction and Customer Loyalty of PT. BPR Prima Multi Makmur. The population is 88 customers with the sampling technique used is the census. Data obtained by using a questionnaire and documentation. The data analysis technique uses path analysis. The results showed that the Customer Value Variable (X2) had a significant and positive influence on the Customer Satisfaction variable (Y1). The Service Quality variable (X1) has a significant positive effect on the Customer Loyalty variable (Y2). The Customer Value variable (X2) has a significant positive effect on the Customer Loyalty variable (Y2). The CRM variable (X3) has a significant positive effect on the Customer Loyalty variable (Y2). The Customer Satisfaction variable (Y1) has a significant positive effect on the Customer Loyalty variable (Y2). Based on the research conclusions, it can be suggested the following: The company, in this case PT. BPR Prima Multi Makmur, must pay attention to the significant pathways in this research in order to add and retain customers better